Teaching about Missing and Murdered Indigenous Women, Girls, and 2SLGBTQQIA+ People: Implications for Canadian Educators - Vanner, Catherine; Goyeau, Jillian; Logan, Meegwun; Ryan, Kendal; Weenie, Angelina; Mitchell, Claudia (Canadian Journal of Education / Revue canadienne de l'éducation)

(untitled) (Canadian Society for the Study of Education, 2024)
The 2019 National Inquiry on Missing and Murdered Indigenous Women and Girls called on educators at all levels to raise awareness about the phenomenon of missing and murdered Indigenous women, girls, and 2SLGBTQQIA+ people (MMIWG2S) and its root causes as connected to centuries of colonial violence and ongoing systemic discrimination. This article responds to that call by showcasing the experiences of eight teachers already teaching about MMIWG2S, the recommendations of 11 adolescent Indigenous girl activists, and the guidance provided in the Their Voices Will Guide Us teaching and learning guide, published alongside the National Inquiry’s final report. We draw upon the combined perspectives to encourage teachers in Canada to address the issue of MMIWG2S with their students, moving past representations of colonial violence as historical to examining how it affects the lives and deaths of far too many Indigenous people in Canada today.